Legal Analysis Regarding Police Authority In Collecting Debt Based On Government Regulation Number 2 Of 2003 Concerning Disciplinary Regulations For Members Of The Indonesian National Police - Maston, Maston; Risdaina, Risdaina; Kumalasari M, Indra (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2023)
based on Government Regulation Number 2 of 2003 concerning Disciplinary Regulations for Members of the Indonesian National Police. As well as knowing and analyzing the authority of the police in collecting debts. This research is a type of normative research. So that it can be seen that all police authority is based on Government Regulation Number 2 of 2003 concerning Disciplinary Regulations for Members of the Indonesian National Police. In addition, no one can ask the police to collect debts because it is against the Police Discipline Regulations. If in practice it is found that police act in this way, the aggrieved party can report the member of the police to the Professional and Security Division of the National Police.